STUDY OF CYCLIC HOT CORROSION RESISTANCE OF AL0,75COCRFENI HIGH ENTROPY ALLOY INDUCED BY MIXTURE OF NA2SO4 AND V2O5 MOLTEN SALT AT 1000? - Abdul Aziz, Adrianza
High entropy alloys are highly potentially used in high temperature applications due to their good mechanical properties and good thermal stability. Al0,75CoCrFeNi alloy is one example of a high entropy alloy consisting of transitional metals at a relatively cheap price and potentially to be used in the aerospace field, for example as a material for the manufacture of turbine blade on aircraft engines operating at high temperature. A common problem with turbine blade operating at high temperature is hot corrosion caused by the presence of contaminants such as salt liquid on the turbine blade. Salt contaminants commonly found on turbine blade in aircraft engines are Na2SO4 and V2O5. The experiment was conducted to study the cyclic hot corrosion resistance of the Al0,75CoCrFeNi high entropy alloy induced by mixture of Na2SO4 and V2O5 molten salt at 1000?. The experiment started with the melting of the alloying elements in an inert atmosphere. The alloy from the melting was obtained in form of button. The alloy button was then homogenized at 1100°C for 10 hours in an inert atmosphere. After that, the button was cut to obtain the small coupons and cutting residue alloy. Cutting residue alloy was characterized by SEM to observe as-homogenized alloy microstructure. The coupons were used for cyclic hot corrosion tests with variations of 5, 10, 15, and 25 cycles. Each cycle was conducted by heating for 1 hour at 1000? and air cooling for 15 minutes. The change in coupons weight were measured at every single test cycle. After the test, coupons were then characterized by XRD and SEM to determine the phase formed on the alloy surface, observe the morphology of the alloy surface, and observe alloy cross section. Based on the results of the characterization, it was obtained that the as-homogenized alloy has a lamellar shaped FCC phase, lamellar shaped BCC phase, and droplet shaped BCC phase. On the surface of the alloy, the oxide phases consist of FeV2O4, (Co,Fe,Ni)Cr2O4, AlFe2O4, Fe2O3, Fe3O4, V2O5, and NaVO3 were found. Cross section of the alloy showed the formation of porous and non-continuous Cr-rich oxides on alloy surface and the spread of sulfides of Al and Cr near alloy surface. Data on alloy weight changes during the hot corrosion test showed an increase in weight until the 3rd cycle continued with a decrease in weight up to the 25th cycle. Al-rich and Cr-rich oxides formed predominantly at the beginning of the test and then the depletion of Al and Cr at the alloy surface caused the oxides of other metals to form easily. During the hot corrosion test there were repeated phenomena on the alloy such as oxidation, sulfidation, dissolution of oxide, and spallation of oxide.